Thermal-induced upheaval buckling of continuously-reinforced semi-infinite concrete pavements. (1st August 2018) - Yang, Guotao; Bradford, Mark A.
Highlights: Heavy pavement thermal upheaval buckling represented in analytical form. Stiffness of pavement base included in formulation. Solutions are provided for a pavement with a rigid medium. Technique provides a means of vulnerability assessment for pavements in prolonged heatwaves. Abstract: In some configuration cases for concrete pavements, such as at the intersection of two road pavements or the connection of a road pavement to a bridge abutment, the pavement can be considered to be semi-infinite with one end adjoining a rigid structure. In addition, continuously reinforced concrete pavements may weaken over time as a result of corrosion, erosion, shrinkage, fatigue cracking or the like, and in these instances the weakened pavement can also be considered as being semi-infinite with a joint. This rotational joint constrains the end of the pavement, which has an effect on the potential upheaval buckling of the pavement when subjected to heatwaves. This paper presents an analytical solution for thermal-induced upheaval buckling of such a semiinfinite continuously reinforced concrete pavement when constrained by a rigid medium with a quantifiable rotational stiffness. The method of minimum total potential energy is invoked to derive the differential equations for the post-buckling response, and the equilibrium equations with variable parameters that govern the behaviour are solved analytically by considering both the deformation of the pavement and the rotational and translational restraints. Parametric investigations are conducted on the buckling response of the pavement when constrained at one end; the parameters considered being the rotational stiffness of the joint, the thickness of the pavement, the properties of the pavement subgrade base and the effective weight of the pavement. It is found that the constraint affects the buckling temperature considerably, and the so-called safe temperature increases with the rotational stiffness of the constraint the end of the pavement.